Service Quality on Purchasing Decisions at Minimarket 212 Mart, Tampan District - Rico Sandy Napitupulu; Almasdi Syahza; Mujiono Mujiono (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine the effect of service quality on purchasing decisions at Minimarket 212 Mart, Tampan District. The method used in this study is a quantitative descriptive method with a total sample of 90 people. The data collection instrument used in this study was a questionnaire using a Likert scale. The data analysis technique used is simple linear regression. The results of this study obtained indicate that service quality has a positive and significant effect on purchasing decisions with the regression equation Y = 7.633 + 0.196 and contributes 39.8% and the rest is influenced by other factors not examined.